EXECUTER1 and singlet oxygen signaling: A reassessment of nuclear activity - Liu, Kaiwei; Zhao, Huan; Lee, Keun Pyo; Yu, Qing; Di, Minghui; Wang, Liangsheng; Kim, Chanhong (The Plant cell, 2024)
Chloroplasts are recognized as environmental sensors, capable of translating environmental fluctuations into diverse signals to communicate with the nucleus. Among the reactive oxygen species produced in chloroplasts, singlet oxygen (1O2) has been extensively studied due to its dual roles, encompassing both damage and signaling activities, and the availability of conditional mutants overproducing 1O2 in chloroplasts. In particular, investigating the Arabidopsis (Arabidopsis thaliana) mutant known as fluorescent (flu) has led to the discovery of EXECUTER1 (EX1), a plastid 1O2 sensor residing in the grana margin of the thylakoid membrane. 1O2-triggered EX1 degradation is critical for the induction of 1O2-responsive nuclear genes (SOrNGs). However, a recent study showed that EX1 relocates from chloroplasts to the nucleus upon 1O2 release, where it interacts with WRKY18 and WRKY40 (WRKY18/40) transcription factors to regulate SOrNG expression. In this study, we challenge this assertion. Our confocal microscopy analysis and subcellular fractionation assays demonstrate that EX1 does not accumulate in the nucleus. While EX1 appears in nuclear fractions, subsequent thermolysin treatment assays indicate that it adheres to the outer nuclear region rather than localizing inside the nucleus. Furthermore, luciferase complementation imaging and yeast 2-hybrid assays reveal that EX1 does not interact with nuclear WRKY18/40. Consequently, our study refines the current model of 1O2 signaling by ruling out the nuclear relocation of intact EX1 as a means of communication between the chloroplast and nucleus.